Recuperación de la Cartera vencida del GAD del cantón Montalvo periodo 2020 - Chiriboga Villacis, Eduardo Xavier (2021)
The purpose of this case study is to show the problems faced by the Decentralized Autonomous Government of the Montalvo canton with RUC 1260000490001 in relation to the past due portfolio. The past due portfolio represents a problem for public sector entities as well as for the private sector and they are obligations that people have with an entity and they were not carried out within the established deadlines and they become a problem since they are securities that have not been able to recover. The research method to be used in this work is the inductive and investigative method that will allow interviews to be carried out with the people who work in the institution and obtain physical and digital documentation, which evidences what is really happening in the entity and thus have a better perspective of why you have an overdue portfolio. After having carefully reviewed, I concluded that the taxpayers of the Montalvo canton do not make their respective payments for municipal licenses, urban properties, rustic properties and other items for water, sewage and garbage.